Exposure to IQOS ads and reduced exposure claims, and association with perceived risk from COVID-19 on IQOS purchase and use intentions: results from a web-based survey - Sharma, Akshika; Fix, Brian; Hyland, Andrew; Bansal-Travers, Maansi; Quisenberry, Amanda; O’Connor, Richard (Frontiers in Public Health, 2024)
Introduction IQOS was authorized to be marketed as a reduced exposure product by the Food and Drug Administration in October 2020 during the global COVID-19 pandemic. Those who smoke may be more sensitive to reduced exposure marketing claims and may have an increased inclination toward IQOS use. We evaluated the likelihood of trying and purchasing IQOS as a function of exposure to ads, product appeal, and COVID-19 risk perceptions using the original IQOS ads with reduced exposure marketing. Method An online cross-sectional survey recruited 604 US adults (18–45 years), both who smoke and do not smoke. Participants saw one of the six randomly assigned IQOS ads with or without reduced exposure claims, and they answered questions about product appeal and likelihood to try and purchase IQOS. Generalized linear models were used to examine associations. Results A per unit increase in product appeal was associated with a greater likelihood of purchasing (B = 0.17, 95% CI: 0.15–0.18) and trying IQOS (B = 0.16, 95% CI = 0.14–0.18). Current smokers and former e-cigarette users reported greater intentions to try IQOS than never-smokers and never e-cigarette users, respectively. Likelihood to purchase IQOS was associated with greater confidence in not contracting COVID-19 (B = 0.11, 95% CI: 0.01–0.21). No significant differences were observed between different ad conditions. Current (B = −0.34, 95% CI = −0.50-(−0.19)) and former (B = −0.92, 95% CI = −0.15-(−0.68)) cigarette smokers who were someday e-cigarette users reported less intentions to purchase IQOS than never e-cigarette users. However, never smokers who were someday (B = 0.58, 95% CI = 0.27–0.89; B = 0.68, 95% CI = 0.39–0.98) and former e-cigarette (B = 0.38, 95% CI = 0.15–0.61) users reported greater intentions to purchase and try IQOS, respectively. Discussion IQOS may have a higher product appeal, especially for those who currently smoke and those who have lower risk perceptions from COVID-19. Among never smokers, those who currently use or have used e-cigarettes in the past may be more receptive to IQOS marketing. The data are informative for potential trends in the use of IQOS in the future and may have implications for marketing regulations of heated tobacco products (HTPs).